Analisis Evaluasi Pengawasan Dana Zakat Produktif Dalam Pengembangan Usaha Bagi Mustahik Di Lazismu Kota Medan - Yati Pratiwi Hasibuan; Muti’ah Khaira Sihotang (Al-Sharf: Jurnal Ekonomi Islam, 2023)
The objectives to be achieved from this research are to find out the supervisory system in managing Productive Zakat at Lazismu Medan City and to find out how the monitoring standards and process of zakat funds are at Lazismu Medan City. This study uses a qualitative approach. The results of the study show that supervision is one of the management functions that needs to be pursued in achieving effective organizational goals. Supervision is a preventive process in an effort to achieve positive activities and prevent actions that violate the rules. Prevention of acts that violate the rules in the language of the Islamic religion is also called "Amar Ma'ruf Nahi Munkar". Supervision standards in LAZISMU Medan City are in the form of targets, quotas and implementation budgets. This is stated in the work program planning of each unit or field. All distribution of funds is in accordance with the mandate of the muzakki where they want the funds to be distributed. Professional/income zakat funds will be channeled to groups entitled to receive zakat, infaq funds will be distributed to several existing LAZISMU programs.